Father Ong as Cultural Critic - Harp, Jerry (Christianity & literature, 2018)
Walter J. Ong is well known for his in-depth work in studies of orality and literacy. This article proposes reading Ong in more expansive terms, as a cultural critic with a wide range of knowledge and a deep sense that all things are connected. This conviction of all things' interrelationship, combined with the sense that, in the words of Gerard Manley Hopkins, all the world is charged with the grandeur of God, yielded in Ong insights into a broad array of subjects. Many of these insights grow out of, but are not limited to, his orality-literacy studies.